Waist-to-height-ratio is associated with sustained hypertension in children and adolescents with high office blood pressure - Nimkarn, Norrarath; Sewarit, Anyamanee; Pirojsakul, Kwanchai; Paksi, Witchuri; Chantarogh, Songkiat; Saisawat, Pawaree; Tangnararatchakit, Kanchana (Frontiers in Cardiovascular Medicine, 2023)
Background Waist-to-height-ratio (WHtR) has been proposed as another indicator for cardiometabolic risk factors including hypertension. Normally, hypertension can be diagnosed in the office setting by detecting high blood pressure for three occasions. However, patients with high office blood pressure may not exhibit high blood pressure outside the office. Ambulatory blood pressure monitoring (ABPM) is a procedure to measure blood pressure over 24-h. Sustained hypertension is characterized as hypertension detected by both office measurement and ABPM. This study aimed to evaluate the performance of WHtR in the diagnosis of sustained hypertension in patients with high office blood pressure. Materials and methods Demographic data, height, body weight, body mass index (BMI), and waist circumference were retrospectively reviewed in children and adolescents who underwent ABPM due to persistently high office blood pressure. Patients were separated into two groups: a sustained hypertension group and a normal ABPM group. BMI was adjusted to z-score using the WHO Anthroplus software. WHtR was calculated by the formula: waist circumference (cm)/height (m). The performances of different parameters were analyzed using the receiver operating characteristic (ROC) curve and multivariate logistic regression. Results Sixty patients (63% male) with a mean age of 12.9 ± 3.7 years had persistently high office blood pressure. Twenty-nine (48.3%) had high ambulatory blood pressure parameters so-called “sustained hypertension.” The sustained hypertension group had a higher mean BMI z-score (2.32 vs. 1.31, p = 0.01) and a higher mean WHtR (57.7 vs. 49.2 cm/m, p < 0.001) than those of the normal ABPM group. For the diagnosis of sustained hypertension, the ROC analysis revealed that WHtR had a greater area under the ROC curve (AUC) than that of BMI z-score (0.772 vs. 0.723). WHtR remained associated with sustained hypertension (OR 1.2, 95% CI 1.022–1.408, p = 0.026) after adjusting for age, gender, and BMI z-score. Conclusions Apart from being a more user-friendly metric, WHtR tended to outperform BMI z-score in predicting sustained hypertension in children and adolescents with persistently high office blood pressure.